Comparison of the Effects of Two Diets Rich in Monounsaturated Fatty Acids Differing in their Linoleic/α-Linolenic Acid Ratio on Platelet Aggregation - Freese, Riitta; Mutanen, Marja; Valsta, Liisa M; Salminen, Irma (Thrombosis and Haemostasis, 1994)
The effect of dietary linoleic/α-linolenic acid ratio on human platelet aggregation in vitro was investigated using low-erucic acid rapeseed oil and high-oleic acid sunflower oil as the major fat sources. In a cross-over study 20 healthy male subjects, average age 29 year (range 20–46 yr), followed experimental rapeseed oil (RO) and Trisun-sunflower oil (TSO) diets after their habitual diet for six weeks. Subjects were provided most of the fat containing foods but were allowed to eat other foods almost freely. Fatty acid compositions of the diets calculated from dietary records were as follows (saturated/monounsaturated/polyunsaturated fatty acids): RO diet 12.4/18.6/8.9% of total energy (en%) (linoleic/α-linolenic acid ratio 2.8) and TSO diet 11.8/17.8/8.3 en% (linoleic/α-linolenic acid ratio 28), respectively. Plasma cholesterol ester fatty acid composition proved compliance to the experimental diets. Platelet aggregations induced by ADP (1,2 and 3 μM) or thrombin (0.12, 0.15 and 0.18 NIH/ml) were significantly enhanced and collagen- (1.5, 2.5 and 5.0 μg/ml) induced aggregation tended to be enhanced after the TSO diet compared with the RO diet. After the TSO diet platelet aggregation was enhanced from the level of the habitual diets by one thrombin (0.18 NIH/ml), one collagen (1.5 μg/ml) and all three ADP concentrations. The diets had no effect on antithrombin III activity. Results show that platelet aggregation in vitro decreases as the ratio of linoleic acid to a-linolenic acid decreases in diets rich in monounsaturated fatty acids.